Implikasi Nilai dalam Proses Pendidikan Islam - Aziz, Abd. (Ta'allum: Jurnal Pendidikan Islam, 2013)
Merit can be understood as the standard of how human being behaves in relation to others. Merit or moral value can be classified in some categories depending on the perspectives by which such merit is viewed. In general, merit is classified into two, namely formal and material. This writing is intended to discuss how such classification works within the context of Islamic education. It is believed that Islamic merit only remains as subject matter but it is not internalized into students’ way of life. Thus, even though students achieve high scores in their Islamic subject matter, their behaviour is not acceptable in the society.